Progesterone receptor expression in proliferating cancer cells of hormone-receptor-positive breast cancer. Issue 10 (November 2018) - Ueno, Takayuki; Saji, Shigehira; Chiba, Tomohiro; Kamma, Hiroshi; Isaka, Hirotsugu; Itoh, Hiroki; Imi, Kentaro; Miyamoto, Kaisuke; Tada, Manami; Sasano, Hironobu; Toi, Masakazu; Imoto, Shigeru
Breast cancer has been suggested to have two distinct driving mechanisms: the hormone receptor and the growth factor receptor pathways. We hypothesized that each driving system produces a different expression pattern of estrogen-regulated genes, such as progesterone receptor, in proliferating cells. Progesterone receptor and Ki67 expressions were assessed by dual-fluorescence immunohistochemistry in estrogen-receptor-positive breast cancer tissues. Two distinct proliferating cell populations were observed: progesterone-receptor-positive and progesterone-receptor-negative. In the training cohort, tissues with progesterone-receptor-positive proliferating cells were associated with lower grade and better disease-free survival (p = 0.0055 and 0.0026, respectively). These associations were confirmed in the validation cohort from the neoadjuvant endocrine trial JFMC34 (p = 0.033 and 0.0003, respectively). In the validation cohort, patients with progesterone-receptor-positive proliferating cells responded better to endocrine therapy and had a lower Oncotype DX Recurrence Score. In the multivariate analysis, progesterone receptor status of proliferating cells, but not progesterone receptor or Ki67 alone, was an independent predictor of disease-free survival in both cohorts (p = 0.0043 and 0.0026). In conclusion, the progesterone receptor status of proliferating cancer cells was associated with histological grade and Recurrence Score, and a potent prognostic factor in estrogen-receptor-positive breast cancers. Results suggest that different driving systems generate different expression patterns of progesterone receptor in proliferating cancer cells. Further studies are warranted to validate the findings.